A highly CO-tolerant atomically dispersed Pt catalyst for chemoselective hydrogenation - Lin, Lili; Yao, Siyu; Gao, Rui; Liang, Xuan; Yu, Qiaolin; Deng, Yuchen; Liu, Jinjia; Peng, Mi; Jiang, Zheng; Li, Siwei; Li, Yong-Wang; Wen, Xiao-Dong; et al. (Nature nanotechnology, 2019)
The hydrogenation activity of noble metal, especially platinum (Pt), catalysts can be easily inhibited by the presence of a trace amount of carbon monoxide (CO) in the reaction feeds. Developing CO-resistant hydrogenation catalysts with both high activity and selectivity is of great economic interest for industry as it allows the use of cheap crude hydrogen and avoids costly product separation. Here we show that atomically dispersed Pt over α-molybdenum carbide (α-MoC) constitutes a highly CO-resistant catalyst for the chemoselective hydrogenation of nitrobenzene derivatives. The Pt 1 /α-MoC catalyst shows promising activity in the presence of 5,000 ppm CO, and has a strong chemospecificity towards the hydrogenation of nitro groups. With the assistance of water, high hydrogenation activity can also be achieved using CO and water as a hydrogen source, without sacrificing selectivity and stability. The weakened CO binding over the electron-deficient Pt single atom and a new reaction pathway for nitro group hydrogenation confer high CO resistivity and chemoselectivity on the catalyst. Atomically dispersed Pt on an α-MoC support exhibits high CO tolerance during selective hydrogenation of nitrobenzene and its derivatives.